Short-term results of community-based interventions for improving physical activity: Isfahan Healthy Heart Programme - Rabiei, Katayoun; Kelishadi, Roya; Sarrafzadegan, Nizal; Sadri, Gholamhossein; Amani, Ahmad (Archives of Medical Science, 2010)
Introduction: To assess the effect of a comprehensive community-based programme for increasing physical activity (PA) after 2 years of interventions. Material and methods: A 6-year, action-oriented, comprehensive, and integrated community-based study, entitled the Isfahan Healthy Heart Programme, was conducted in Iran from the year 2000. The interventions targeted the whole population of nearly 2,180,000 living in two cities, and were compared with another city considered as a reference. Educational, environmental and legislative interventions were conducted at the community level. Annual evaluations were performed among 6,000 representative individuals. This paper presents the changes in PA habits after 2 years of interventions for increasing PA. The PA habits were assessed by using the Baecke questionnaire, and an energy expenditure of 150 kcal for daily leisure time physical activity was adopted as a cut-off for defining active and inactive lifestyle. Results: In the intervention and reference areas, respectively 85 and 83% of the population were physically inactive. From 2000 to 2002, the daily PA among both genders decreased in both intervention and reference communities. Meanwhile, the leisure-time PA increased significantly in the intervention area, but decreased in the reference area. The transportation PA did not significantly change in the intervention area, but showed a remarkable decline in the reference area. Conclusions: We suggest that the synergism resulting from community collaborations has been effective in improving some aspects of PA in our community. The ongoing changes in environmental factors and policies can help in increasing the worksite and transportation PA in later stages of this community-based programme.